Determination of Inheritance Rights for Transgender Individuals According to Positive Law in Indonesia - Dian Ayu Rizkika; Gunawan Djajaputra (JUSTISI, 2025)
This study aims to analyse the legal position of transgender inheritance in the inheritance system in Indonesia concerning customary law, the Compilation of Islamic Law, and applicable civil law. This study uses a normative legal method with a regulatory-legislative approach and a contextual approach. The data sources used include relevant laws and regulations, Islamic legal doctrines, and court decisions related to transgender inheritance cases in Indonesia. The analysis examined the relationship between applicable legal provisions and legal practices in society. The novelty of this study lies in a comprehensive analysis of the position of transgender people in Indonesian inheritance law and the identification of alternative solutions outside the conventional inheritance system. The results of this study reveal that although Islamic law does not recognise gender change about inheritance status, there is no explicit prohibition in the KHI regarding the distribution of inheritance to transgender people. Therefore, mechanisms such as grants, agreements, and wills are legal alternatives that can be used to provide part of the property to transgender people in a family. The results of the study indicate that in the legal system in Indonesia, transgender people do not have specifically recognised inheritance rights. However, legal provisions allow the use of other instruments such as grants and wills to provide property to transgenders without violating the principles of Islamic law or positive law. The study concluded that although there are no explicit regulations regarding inheritance rights for transgender individuals, alternative mechanisms in Indonesian inheritance law can be used to ensure justice for all parties. Therefore, more inclusive legal policies are needed so that this issue can be adequately accommodated in the national legal system.